Residual Strength Analysisof Asymmetrically Damaged Ship Hull GirderUsing Beam Finite Element Method - Alie, Muhammad Zubair Muis (Makara Journal of Technology, 2016)
The objective of the present study is to analyze the residual strength of asymmetrically damaged ship hull girder under longitudinal bending. Beam Finite Element Method is used for the assessment of the residual strength of two single hull bulk carriers (Ship B1 and Ship B4) and a three-cargo-hold model of a single-side Panamax Bulk Carrier in hogging and sagging conditions. The Smith’s method is adopted and implemented into Beam Finite Element Method. An efficient solution procedure is applied; i.e. by assuming the cross section remains plane, the vertical bending moment is applied to the cross section and three-cargo-hold model. As a fundamental case, the damage is simply created by removing the elements from the cross section, neglecting any welding residual stress and initial imperfection. Also no crack extension is considered. The result obtained by Beam Finite Element Method so-called Beam-HULLST is compared to the progressive collapse analysis obtained by HULLST for the validation of the present work. Then, for the three-hold-model, the Beam-HULLST is used to investigate the effect of the rotation of the netral axis both intact and damage condition taking the one and five frame spaces into account.